Ganho genético para produtividade de grãos de milho na região sul do Brasil - Silva, Éder David Borges da (2015)
The objectives of this study was to calculate the genetic gain corn grain yield in southern Brazil and calculate the genetic gain in two classes of altitude. The methods used were the Vencovsky et al. (1988) based on linear models with inference least squares (ML/MQ) and the Borges et al. (2009), based on mixed models with inference by residual likelihood (MM/REML). We used a database with 30,292 yield observation from corn grain but resulting in 135 genotypes in 2,826 trials conducted in 13 years, from 2001 to 2013, being the year regarding the planting date of the trials. For the stratification of trials, in order to form similar environments, we used as criteria the altitude, down and up to 700m. The methodology of ML/MQ annual mean genetic gain was 121 kg ha-1 year-1 with a confidence interval to 95% [11;232] kg ha-1 year-1, and by MM/REML methodology was 79 kg ha-1 year-1 with a confidence interval to 95% [70; 98] kg ha-1 year-1 for the entire southern region of Brazil. In regions with altitude of 700 m, the genetic gain was 94 kg ha-1 year-1 and in regions with altitude less than 700 mo genetic gain was 74 kg ha-1 year-1.MM/REML methodology provided intervals more accurate and reliable values of genetic gain lower when compared to ML/MQ methodology. In all cases analyzed, the genetic gain was positive and significant between the years 2001-2013.